The impacts of free trade agreements on economies: the case of Mercosur - Sӧren Alexander, Hoffmann (2018)
Fil: Sӧren Alexander, Hoffmann. University of Applied Sciences Hochschule Kaiserslautern. Faculty of Business Administration; Alemania.